Combination drug therapy by herbal nanomedicine prevent multidrug resistance protein 1: promote apoptosis in Lung Carcinoma - Ashraf Alemi; Mojtaba Haghi Karamallah; Mohamad Sabaghan; Seyed Ahmad Hosseini; Ali Veisi; Somayeh Haghi Karamallah; Mohammad Farokhifar (Journal of Applied Biomaterials & Functional Materials, 2024)
Given the numerous adverse effects of lung cancer treatment, more research on non-toxic medications is urgently needed. Curcumin (CUR) and berberine (BBR) combat drug resistance by controlling the expression of multidrug resistant pump (MDR1). Fascinatingly, combining these medications increases the effectiveness of preventing lung cancer. Their low solubility and poor stability, however, restrict their therapeutic efficacy. Because of the improved bioavailability and increased encapsulation effectiveness of water-insoluble medicines, surfactant-based nanovesicles have recently received a great deal of attention. The current study sought to elucidate the Combination drug therapy by herbal nanomedicine prevent multidrug resistance protein 1: promote apoptosis in Lung Carcinoma. The impact of several tween (20, 60, and 80) types with varied hydrophobic tails on BBR/CUR-TNV was evaluated. Additionally, the MDR1 activity and apoptosis rate of the BBR/CUR-TNV combination therapy were assessed. The encapsulation effectiveness of TNV was affected by the type of tween. With the TNV made from tween 60, cholesterol, and PEG (47.5: 47.5:5), more encapsulation effectiveness was attained. By combining CUR with BBR, especially when given in TNV, apoptosis increased. Additionally, when CUR and BBR were administered in combination, they significantly reduced the risk of MDR1 development. The current work suggests that the delivery of berberine and curcumin as a combination medication therapy via tween-based nanovesicles may be a potential lung cancer treatment.